1980
DOI: 10.1111/j.2044-8279.1980.tb00797.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Locus of Control and Academic Achievement, Anxiety, and Level of Aspiration

Abstract: Summary. While holding the influence of socio‐economic status constant, the relationship between locus of control and academic achievement, anxiety, and level of aspiration was examined among 2,438 ninth grade Israel‐Jewish students of Asian or African background and European, American, or Israeli backgrounds. It was observed that, in general, internals tend to attain greater academic achievement, to express less anxiety, and to have higher level of aspiration. The relationship between academic achievement, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

1983
1983
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
9
0
4
Order By: Relevance
“…Bar-Tal et al (1980) found SES to be correlated positively with internality for both his Asian-African sample (.23, ρ < .001) and his Euro-American-Israeli sample (.21, ρ < .001) Similarly small but significant correlations were found by Lao et al (1977) for their Taiwanese sample. Bar-Tal et al (1980) found SES to be correlated positively with internality for both his Asian-African sample (.23, ρ < .001) and his Euro-American-Israeli sample (.21, ρ < .001) Similarly small but significant correlations were found by Lao et al (1977) for their Taiwanese sample.…”
Section: Loc and Sesmentioning
confidence: 89%
“…Bar-Tal et al (1980) found SES to be correlated positively with internality for both his Asian-African sample (.23, ρ < .001) and his Euro-American-Israeli sample (.21, ρ < .001) Similarly small but significant correlations were found by Lao et al (1977) for their Taiwanese sample. Bar-Tal et al (1980) found SES to be correlated positively with internality for both his Asian-African sample (.23, ρ < .001) and his Euro-American-Israeli sample (.21, ρ < .001) Similarly small but significant correlations were found by Lao et al (1977) for their Taiwanese sample.…”
Section: Loc and Sesmentioning
confidence: 89%
“…Rotter hypothesised that internals would engage themselves more in achievement related activities than externals who tend to feel that they have little control over their rewards and punishments. Several studies (Crandall et al, 1962;Chance, 1965;Crandall et al, 1965;McGhee and Crandall, 1968;Brown and Strickland, 1972;Bar-Tal et al, 1980) have been carried out in Western countries to test this hypothesis. I t was generally found that levels of academic achievement for internals was consistently and significantly higher than those of externals.…”
Section: Introductionmentioning
confidence: 99%
“…Hsieh et al (1969) concluded that individuals raised in a culture that values self-reliance and individualism are likely to be more internally oriented than those brought up in a different set of values. Several researchers (Morrison & Mclntyre, 1971;Phares, 1975;Bar-Tal et al, 1980) suggested that perception of locus of control is an important personality variable that relates to academic success in schools, internals tending to attain greater academic success.…”
mentioning
confidence: 97%